Changing trends in oral mucosal diseases in China (2016–2024): a cross-sectional study of 316,166 patients with focus on COVID-19 impact and use of chinese patent medicines - Peiru Zhou; Xu Zhang; Yifan Chen; Jiakun Fang; Yanhong Meng; Furong Yang; Pan Wei; Hong Hua (BMC Oral Health)
Abstract Background Oral mucosal health is a critical component of overall oral health and impacts an individual’s quality of life. Despite variations in prevalence rates of oral mucosal diseases across regions, previous studies often involved small sample sizes with insufficient data analysis. This study addresses the gap by providing a comprehensive analysis of the changing spectrum of oral mucosal diseases in China, with a focus on the impact of COVID-19. It also explores trends in the use of Chinese patent medicines (CPMs) for treatment. Methods This retrospective, cross-sectional study included 316,166 patients from the Department of Oral Medicine at Peking University School and Hospital of Stomatology between 2016 and 2024. Data on patient demographics, chief complaints, diagnoses, and the use of CPMs were collected and analyzed. Statistical comparisons were made using t-tests and chi-square tests, with significance set at P < 0.05. Results The average patient age was 49.42 ± 17.92 years, and women were significantly overrepresented (male/female ratio: 0.59). The most frequent diagnoses were oral lichen planus and recurrent aphthous stomatitis, accounting for the top two positions each year. The study found significant differences in disease patterns among age groups, with oral potentially malignant disorders like oral lichen planus becoming more prevalent in older populations. CPMs were used by 52.29% of patients, with similar proportions using topical and systemic treatments. During the COVID-19 pandemic (2020–2022), the number of patients dropped significantly, and an increased prevalence of burning mouth syndrome and oral candidiasis was observed. Conclusion This study offers the largest amount of valuable epidemiological data on the management of oral mucosal diseases to date in China, underscoring the need for targeted health resource allocation. An important trend was the greater predilection for females and middle-aged and elderly populations. The top three diseases in terms of number of patients were oral lichen planus, recurrent aphthous stomatitis, and oral candidiasis. The treatment data indicated widespread use of CPMs for oral mucosal diseases. The COVID-19 pandemic was associated with a significant decrease in the number of total patients and was also characterized by an increase in the proportion of patients with diseases that have psychosomatic associations. The impact of the COVID-19 pandemic and the widespread use of CPMs warrant further investigation in future studies to ensure evidence-based medical practices. Clinical trial number Not applicable.